Optimizing Bio-Oil Yield from Pyrolysis of Spent Bleaching Earth for Liquid Fuel Production - Okzani, Syahrial; Said, Muhammad; Bahrin, David (Universitas Negeri Semarang, 2024)
Spent Bleaching Earth is an industrial waste generated primarily from vegetable oil processing and contains 20-40% oil by weight, which poses a fire hazard due to the risk of spontaneous combustion. Commonly, Spent Bleaching Earth is processed using extraction methods with solvents like n-hexane, methanol, or steam. However, transforming SBE into liquid fuel via pyrolysis remains underexplored. This research aims to convert into liquid fuel through pyrolysis. The process was conducted at 600 °C for 90 min, resulting in pyrolysis oil with a density of 992.8 kg/m³, a viscosity of 31.21 cSt, a calorific value of 40.63 MJ/kg, and a flash point of 36 °C. Additionally, the oil contained 21.18% phenol compounds. The remaining material from the process, including char, constituted 54% of the original spent bleaching earth mass. These results demonstrate the feasibility of using pyrolysis to convert into a valuable liquid fuel, offering a sustainable approach to manage this hazardous industrial waste while producing energy-rich byproducts. This study underscores the potential of pyrolysis as a waste-to-energy solution and a safer alternative to traditional disposal methods for Spent Bleaching Earth.